Cytogenetic Analysis of the Variable Squirrel (Callosciurus finlaysonii Horsfield, 1824) by Conventional Staining, Ag-NOR Staining and Fluorescence in situ Hybridization Techniques - Talumphai, Sucheela; Khenwiset, Somkiat; Ditcharoen, Sukhonthip; Tanomthong, Alongkload (Journal of Applied Research on Science and Technology (JARST), 2021)
Variable Squirrel belong to the genus Callosciurus which has several color patterns as well as and difficult to classify from other species. Cytogenetics is the study of chromosomal features as useful tool on taxonomic and evolutionary studies of squirrel. Moreover, there are scarcely records of cytogenetics of this squirrel. Therefore, the purpose of the present study are to establish karyotype and ideogram, to investigate the NOR site and the pattern of microsatellite sequence (GC)15 and (CGG)10 using convention staining, Ag-NOR staining, and fluorescence in situ hybridization techniques. The result showed that the diploid chromosome (2n) of C. finlaysonii was 40, the fundamental number was 74 in both sexes, and the sex determination was XY sex-determination system. The karyotype was composed of 4 large metacentric, 8 large submetacentric, 8 large acrocentric, 2 medium submetacentric, 2 medium acrocentric, 2 medium telocentric, 4 small metacentric, 2 small submetacentric, 2 small acrocentric and 4 small telocentric chromosomes. X chromosome was medium metacentric and Y chromosome was small metacentric chromosomes. NOR’s were located on chromosome pairs 14, and microsatellite (GC)15 and (CGG)10 repeats were highly scattered of all chromosome pairs throughout whole genome. This result was able to study evolutionary of squirrel’s chromosome compare with the ancestors. The karyotype formula was 2n (40) = Lm 4 + Lsm 8- + La 8 + Msm 2 + Ma 2 + Mt 2 + Sm 4 + Ssm 2 + Sa 2 + St 4 + sex chromosome. This cytogenetic data provides useful basic information for further study on the comparison of evolutionary relationship and cytotaxonomy in the genus Callosciurus.